Pelatihan Pengembangan Tanaman Obat Keluarga Melalui Peran Serta Masyarakat Di Kampung Seuriget Kecamatan Langsa Barat - Syardiansah Syardiansah; Ayu Artlinta; Suri Amilia; Rahmi Meutia (Pelita Masyarakat, 2021)
The purpose of training the development of family medicinal plants through the participation of the community in Kampung Seuriget, Langsa Barat Subdistrict is to increase the interest of the community to be able to utilize vacant land around the house or yard so as to produce better use value for daily use from the value of family medicinal plants. economical. This training activity involved villagers as suspicious as especially housewives. The implementation of this training involved partners, namely the Seuriget Health Center in West Langsa District. The training method uses the apprenticeship method (direct guidance and work). The family medicinal plant development training was carried out from 7 February 2017 to 10 April 2017 with details of the activities including: making land for cultivation, plant nurseries and planting medicinal plants. The results obtained by the training participants were that they had begun to be able to prepare the land for the crops in the house and to grow crops according to the type of medicinal plants they were interested in. Furthermore, it is expected that the results of this family medicinal plant can be further processed to be able to become food ingredients or other types of processed products of economic value, not just limited to drugs.